The effect of traffic lights and regulatory statements on the choice between complementary and conventional medicines in Australia: Results from a discrete choice experiment. (January 2015) - Spinks, Jean; Mortimer, Duncan
Abstract: It has been suggested that complementary medicines are currently 'under-regulated' in some countries due to their potential for harm as a direct result from side-effects or interactions; from delaying more effective care; or from the economic cost of purchasing an ineffective or inappropriate treatment. The requirement of additional labelling on complementary medicine products has been suggested in Australia and may provide additional information to consumers at the point of purchase. This paper details a unique way of testing the potential effects on consumer behaviour of including either a traffic light logo or regulatory statement on labels. Using a discrete choice experiment, data were collected in 2012 in a sample of 521 Australians with either type 2 diabetes or cardiovascular disease. We find that additional labelling can affect consumer behaviour, but in unpredictable ways. The results of this experiment are informative to further the dialogue concerning possible regulatory mechanisms. Highlights: Additional labelling on complementary medicines has been proposed as a remedy to market failure. Little is known about the potential effect of such a strategy. A discrete choice experiment was conducted to elicit consumer preferences. Both regulatory statement and traffic lights are likely to affect consumer purchasing decisions.